The Library of the Norwegian University of Science and Technology (NTNU) and its work with Open Science (API Magazin, 2023)
The article describes the library of the Norwegian University of Science and Technology and its work with Open Science. It gives a brief overview over the university and the library and presents the new organisational structure of the library. Afterwards, important strategy documents and guidelines for Open Science, Open Access, and Research Data Management at NTNU are introduced and the practical work with it is described. In the end, a selection of other projects and focus areas are mentioned.
Keywords: Norway; Norwegen; Open Science; NTNU